ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, BIAYA OPERASI BERBANDING PENDAPATAN OPERASI DAN NET INTEREST MARGIN TERHADAP RETURN ON ASSETS PADA BANK-BANK UMUM YANG TERCATAT DI BURSA EFEK INDONESIA - Sri Mulyani; Jaleha - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, This research aimed to analyze the influence of Capital Adequacy Ratio, Loan to Deposit Ratio, Operating Expenses and Operating Income Compared Net Interest Margin Of Return On Assets On Commercial Banks Listed in Indonesia Stock Exchange. The research data is in the form of bank financial statements Indonesian Capital Market Directory (ICMD) are published in the Indonesia Stock Exchange as of December 31 period 2008 - 2012. This research method is descriptive method of research that seeks to describe an event or events that occur in the present , Analysis model is intended to describe the relationship between the dominant variables can affect the performance of commercial banks listed on the Indonesia Stock Exchange in determining the positive and negative banking performance. The results showed that simultaneous variables CAR, LDR, ROA and NIM significant effect on ROA. Variable CAR and LDR partially no significant effect on ROA.